Validation de mesures d’attitude, de motivation et d’anxiété envers la lecture chez des universitaires francophones - Lafontaine, Marc (Canadian Journal of Applied Linguistics, 2008)
This follow-up study was conducted for the purpose of validating three measurement scales in reading: attitudes towards reading in French as a first language (L1), motivation towards reading in English as a second language (L2) and anxiety about having to read in English as a second language (L2). A review of the literature focusing on the notion of affective variables in previous studies highlights inconsistencies in the measured notions, as well as in statistical procedures. After having presented the arguments for using the chosen variables, we describe the study in which 57 speakers of French as a first language, enrolled at university, filled in a 40-item questionnaire. Cronbach’s alpha indicated a modest increase in the internal validity of scales and factorial analysis showed difficulty in distinguishing the notion of the desire to read from the intensity of the efforts. Correlational analysis has allowed further consideration of the three scales, which may be variables that play a promising role in reading.